Preorganized AgI Bimetallic Precursor with Labile Diphosphorus Ligands for a Programmed Synthesis of Organometallic–Organic Hybrid Polymers. Issue 64 (25th October 2017) - Moussa, Mehdi Elsayed; Seidl, Michael; Balázs, Gábor; Zabel, Manfred; Virovets, Alexander V.; Attenberger, Bianca; Schreiner, Andrea; Scheer, Manfred
Abstract: An Ag I dimer capped with labile organometallic diphosphorus ligands [Cp2 Mo2 (CO)4 (η 2 ‐P2 )] (Cp=C5 H5 ) acts as a highly pre‐organized molecular precursor to direct the construction of 1D or 2D, and 3D organometallic–organic hybrid coordination polymers upon reaction with ditopic pyridine‐based linkers. The formation of the supramolecular aggregates can be controlled by the stoichiometry of the organic molecules, and the mechanism is supported by DFT calculations. Abstract : Hybrid Coordinates : An Ag I dimer capped with labile η 2 ‐coordinated organometallic diphosphorus ligands [Cp2 Mo2 (CO)4 (η 2 ‐P2 )] acts as a "preprogrammed" molecular precursor to direct a selective construction of one‐ and multi‐dimensional organometallic–organic hybrid polymers, respectively, upon reaction with ditopic pyridine‐based linkers.